2015
DOI: 10.1016/j.scitotenv.2014.10.045
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of potential transfer of natural and anthropogenic cadmium to plankton communities in the North-West African upwelling

Abstract: A Lagrangian approach based on a physical-biogeochemical modeling was used to compare the potential transfer of cadmium (Cd) from natural and anthropogenic sources to plankton communities (Cd-uptake) in the North-West African upwelling. In this region, coastal upwelling was estimated to be the main natural source of Cd while the most significant anthropogenic source for marine ecosystem is provided by phosphate industry. In our model experiment, Cd-uptake (natural or anthropogenic) in the North-West African up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 98 publications
1
39
0
Order By: Relevance
“…1). However, wind-inducing upwelling of intermediate water along WN African Coast and driving to a re-injection of element (Such as Cadmium) in the surface layer (Auger et al 2015). In the same study, it has been demonstrated that potential phytoplankton Cd-uptake and Cd-bioaccumulation coincide with the upwelling enrichment and dispersion patterns in waters.…”
Section: Metal Accumulation Patternsmentioning
confidence: 79%
See 2 more Smart Citations
“…1). However, wind-inducing upwelling of intermediate water along WN African Coast and driving to a re-injection of element (Such as Cadmium) in the surface layer (Auger et al 2015). In the same study, it has been demonstrated that potential phytoplankton Cd-uptake and Cd-bioaccumulation coincide with the upwelling enrichment and dispersion patterns in waters.…”
Section: Metal Accumulation Patternsmentioning
confidence: 79%
“…These high concentrations of Cd were attributed to natural origins, such as upwelling of deep waters, which takes place along the Western Atlantic coast (Romeo et al 1999). Auger et al (2015), has demonstrated that coastal upwelling in Western Atlantic coast, represent the main natural origin of cadmium enrichment of marine ecosystems, whereas the main anthropogenic origin is the phosphate industry effluents. Actually, Morocco is the second phosphate producer in the world.…”
Section: Metal Accumulation Patternsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, only the deterministic velocity components from the OGCM are used to calculate the trajectories. This is a common approach (e.g., Chen et al, 2003;Pous et al, 2010;Auger et al, 2015) and we recognize its limitation. However, OGCMs include such turbulent mixing as a subgridscale diffusivity, thus its signature is present in the physical and biogeochemical properties interpolated along the Lagrangian trajectories.…”
Section: Description Of the Combined Eulerian-lagrangian Approach Primentioning
confidence: 99%
“…This combined qualitative Eulerian-Lagrangian approach to study biophysical interactions was also used by Auger et al (2015), who released particles nearshore in a region of high cadmium (Cd) concentration, to diagnose the dispersion plume of Cd-rich water in an EBUS. They aimed to identify the source of Cd (natural or anthropogenic) that was bio-accumulating, estimated from Cd concentrations and primary production, along cross-shore trajectories.…”
Section: A Case Study To Assess Biology Along Trajectoriesmentioning
confidence: 99%